Predation risk shapes the degree of placentation in natural populations of live‐bearing fish. (12th March 2020) - Hagmayer, Andres; Furness, Andrew I.; Reznick, David N.; Dekker, Myrthe L.; Pollux, Bart J. A.
Abstract: The placenta is a complex life‐history trait that is ubiquitous across the tree of life. Theory proposes that the placenta evolves in response to high performance‐demanding conditions by shifting maternal investment from pre‐ to post‐fertilisation, thereby reducing a female's reproductive burden during pregnancy. We test this hypothesis by studying populations of the fish species Poeciliopsis retropinna in Costa Rica. We found substantial variation in the degree of placentation among natural populations associated with predation risk: females from high predation populations had significantly higher degrees of placentation compared to low predation females, while number, size and quality of offspring at birth remained unaffected. Moreover, a higher degree of placentation correlated with a lower reproductive burden and hence likely an improved swimming performance during pregnancy. Our study advances an adaptive explanation for why the placenta evolves by arguing that an increased degree of placentation offers a selective advantage in high predation environments. Abstract : The degree of placentation (i.e. Matrotrophy Index) in the placental live‐bearing fish species Poeciliopsis retropinna is associated with predation risk. Specifically, females from high predation localities exhibit a significantly higher degree of placentation, compared to females from low predation populations.